2009
DOI: 10.1088/0957-4484/20/35/355304
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced micron and submicron ordering effects in quasi-percolated nanostructured silver thin films

Abstract: Quasi-percolated nanostructured silver thin films are used as the starting morphology for inducing simultaneously changes in shape and ordering effects by laser irradiation. The complex fingered nanostructures are transformed into nanospheres which in turn are arranged in micro-circular patterns when irradiated through a pinhole. These transformations are characterized by transmission electron microscopy and atomic force microscopy. The observed effects are explained using Fresnel diffraction theory. Good agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
4
0
4
Order By: Relevance
“…A). It is possible that this concentric pattern is caused by the diffraction of the incident laser beam as was reported earlier in Haro‐Poniatowski et al . and Haro‐Poniatowski et al .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A). It is possible that this concentric pattern is caused by the diffraction of the incident laser beam as was reported earlier in Haro‐Poniatowski et al . and Haro‐Poniatowski et al .…”
Section: Resultsmentioning
confidence: 96%
“…and/or interference with the beam scattered on surface inhomogeneities with a beam scattered on the edge of the contact mask. As was introduced earlier, the patterning of silver quasi‐percolated thin films through a razor edge or a single slit have shown that the experimental results can be described using Fresnel diffraction theory, the concentric ring pattern was described for several substrates and conditions . The case of circular apertures is mathematically more complex .…”
Section: Resultsmentioning
confidence: 96%
“…The Au nanoclusters (20–40 nm) produced in this way have a surface density in the range (0.2–2) × 10 10 cm −2 , which is sufficient for enhancement of the optical signal. Similarly, improved sensor performance is observed for electrodes modified by deposition of catalytic metals by means of a direct laser transfer of material [ 15 ]. Among metallic structures showing the SPR effect, Au NPs play important role in the construction of electrochemical sensors [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…For thin, granular Au films, the photothermal effect at a wavelength corresponding to the surface plasmon resonance (SPR) peak around 520 nm resulted in the observable decrease of the film roughness and resistivity [ 14 ]. In case of nanostructuring of a thin Au film by a pulsed-laser beam passing through a pinhole (60 μm), the forced arrangement of nanospheres into micro-circular patterns due to diffraction was observed [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…En las regiones de baja intensidad de radiación, no hubo transformación del material, quedando la plata en su estado inicial (cuasipercolado) Fig. 2(c) y en las regiones donde la energía del láser es suficientemente alta para transformar la plata, se forman anillos concéntricos con nanopartículas en su interior que tienen tamaños que van de 75 a los 180 nm de altura y de 100 a 160 nm de diámetro (d) [18]. ii) Bismuto.…”
Section: Oblea De Siliciounclassified